Keeping it Safe: Your Home's Electric System - Mary N. Harrison (EDIS)
This document is FCS5233-01, one of a series of the Department of Family, Youth and Community Sciences, UF/IFAS Extension. Original publication date: May 2002. Revised: December 2005.